Textbook of Community Psychiatry American Association for Community Psychiatry - Sowers, Wesley E.; McQuistion, Hunter L.; Ranz, Jules M.; Feldman, Jacqueline Maus.; Runnels, Patrick S. (Cham : Springer International Publishing : Imprint: Springer, 2022)
The second edition of the AACP's (American Association for Community Psychiatry) Textbook of Community Psychiatry is a welcome update of this notable work that comprehensively presents the state of the art in this field. Along with continuously evolving scientific advances and principles of clinical care, community psychiatry must respond to shifts in public policy as well as economic climate. The past decade has witnessed significant political and social changes, including climate change, immigration levels, technological advancement, the influence of social media and the rise of political unrest. This new edition reflects these wider changes, incorporating new chapters and enhancing previous ones. It remains the standard text for certification of those working in healthcare and social welfare systems design and delivery of services. Readers will gain knowledge of: Basic pillars of the field Evidence based interventions Telepsychiatry and technological aids Trauma informed services Integrated health systems Social determinants of health Structural discrimination.
Part I Introduction and Background -- Introduction: Community Psychiatry on the Move -- History of Community Psychiatry -- Part II The Basics: The Pillars of Community Psychiatry -- Recovery and Person-Centered Care: Empowerment,Collaboration, and Integration -- Population Health, Prevention, and Community Psychiatry -- Exercising Effective Leadership -- Advocacy in Evolution: The Push and Pull of Psychiatrists -- Comprehensive Integrated Systems of Care -- Part III Core Competencies for Community Psychiatrists -- Inspiring a Welcoming, Hopeful Culture -- Motivational Interviewing as a Core Communication Style -- Person-Centered Recovery Planning as a Roadmap to Recovery -- Cultural and Linguistic Competence -- Context-Specific Assessment -- Team Leadership: Promoting Diversity and Inclusion in the Aftermath of COVID-19 -- Community Education -- Collaborative Medication Management and Discontinuation -- Traumatic Stress in the Community: Identification and Intervention -- Integrated Care and Community Psychiatry -- Group Appointments in Psychiatry+ -- Treatment Techniques for Co-occurring Substance -- Use and Mental Disorders -- Women's Mental Health: Core Concepts for Community Psychiatry -- Part IV Effective and Established Interventions -- Developing, Evaluating and Implementing Evidence-Based Interventions in Real World Practice -- Cognitive Behavioral Therapy -- Psychiatric Rehabilitation -- Family Systems Care in Public Sector Settings -- Evidence-Based Practices for Co-occurring Addiction and Mental Illness -- Case Management and Assertive Community Treatment -- Crisis and Emergency Services -- Part V Creating Healthy Communities -- Epidemiology in Community Psychiatry -- Social and Political Determinants of Health and Mental Health -- Mental Health Services Research and Community Psychiatry -- Climate Change: Implications for Community Mental Health -- Disaster Victims and the Response to Trauma -- The Role of the Psychiatrist in Community Consultation and Collaboration -- Collaborative Reduction of Criminal Justice Involvement for Persons with Mental Illness -- Part VI Supportive Services for Community Living -- Housing First and the Role of Psychiatry in Supported Housing -- Health Self-Management: The Emerging Importance of Trauma and Resilience -- Supported Employment -- Peer Service Providers as Colleagues -- Fountain House and the Clubhouse Movement -- Service Coordination and Health Homes -- Part VII Special Populations -- Community-Based Psychiatric Care for Individuals with Intellectual and Developmental Disabilities -- Psychiatric Care for People Experiencing Homelessness -- Early Psychosis and the Prevention and Mitigation of Serious Mental Illness -- Cognitive Behavior Therapy for Psychosis -- Veterans' Services -- Child and Adolescent Psychiatric Services -- Serving Elders in the Public Sector -- Rural Populations.-Clinical Issues and Programming for Sexual and Gender Minority Populations -- Migrant and Refugee Mental Health -- Part VIII Development and Administration of Services -- Transforming Mental Health Systems and Programs -- Program Evaluation -- Creating Value: Resource and Quality Management -- Telehealth and Technology -- The Medical Director in Community-Based -- Mental Healthcare -- Financing of Community Behavioral Health Services -- Workforce Development in Community Psychiatry -- Practical Ethics for Practicing Clinicians -- Part IX Shaping the Future -- Medical Student and Resident Education in Community Psychiatry -- Public/Community Psychiatry Fellowships -- Mentoring and Supervision in Community Psychiatry -- International Trends in Community Mental Health Services -- Community Psychiatry: Past, Present, and Future.
Keywords: Clinical psychology; Community psychology; Clinical Psychology; Community Psychology